Adhesive composition and adhesive sheet
Patent Information
- Application Number
- JP2025062498
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0016】 本発明によれば、粘着剤組成物に温度応答性ポリマーを含むことにより、前記粘着剤組成物から形成される粘着剤層を有する粘着シートは、アルカリ温水中で速やかに被着体から剥離することを見出した。
Smart Images

Figure 2026168930000001 
Figure 2026168930000002 
Figure 2026168930000003
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition and an adhesive sheet.
Background Art
[0002] Adhesive sheets are used for labels to be attached to various containers such as glass bottles for beer, sake and the like, and plastic bottles such as PET bottles. In recent years, container recycling has been promoted due to growing environmental awareness. In order to reuse a container to which an adhesive sheet is attached, the adhesive sheet needs to be removed, but problems such as adhesive residue and base material breakage when the adhesive sheet is peeled off have hindered container recycling. To solve such problems, a method is used in which an adhesive sheet having a water-soluble adhesive layer is used, and the adhesive sheet is peeled off from the container (adherend) by immersion in warm water or alkaline water.
[0003] Examples of adhesives that impart water solubility to the adhesive layer include water-soluble starch-based adhesives and polyvinyl alcohol-based adhesives, and it is known that the use of these adhesives allows the adhesive sheet to be easily peeled off in warm water or alkaline water (see, for example, Patent Document 1). Further, regarding (meth)acrylic adhesives, it has also been proposed to introduce a relatively large amount of carboxyl groups to enhance the water solubility of the polymer, and further improve the water solubility by neutralization with an alkali (see, for example, Patent Document 2).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of Invention
Problems to be Solved by the Invention
[0005] In the process of peeling adhesive sheets from containers (adhered objects), speed of peeling is also required. However, although the adhesives described in Patent Documents 1 and 2 are water-soluble, the rate at which the adhesive layer dissolves in water is not sufficiently fast, and even in the peeling process using alkaline hot water, short-time immersion treatment was insufficient for peeling.
[0006] This invention has been made in view of the above circumstances, and aims to provide an adhesive composition that can be quickly peeled off from an adherend in alkaline hot water, and an adhesive sheet having an adhesive layer formed from the adhesive composition. [Means for solving the problem]
[0007] As a result of their investigations to solve the above problems, the inventors of the present invention found that the above problems can be solved by the adhesive composition described below, and thus completed the present invention. The present invention is, for example, as follows:
[0008] [1] The polymer comprises a (meth)acrylic polymer, a temperature-responsive polymer having a lower critical solution temperature, and a crosslinking agent. The temperature-responsive polymer is a polymer of a monomer component comprising at least one selected from the group consisting of N-substituted (meth)acrylamide monomers and vinyl ether monomers, in an adhesive composition.
[0009] [2] The adhesive composition according to [1], comprising 0.5 to 30 parts by mass of the temperature-responsive polymer per 100 parts by mass of the (meth)acrylic polymer.
[0010] [3] The adhesive composition according to [1] or [2], wherein the temperature-responsive polymer is a polymer of a monomer component containing the N-substituted (meth)acrylamide monomer.
[0011] [4] The adhesive composition according to any one of [1] to [3], wherein the (meth)acrylic polymer is a copolymer of monomer components containing 0.1 to 10% by mass of an amino group-containing monomer.
[0012] [5] The adhesive composition according to any one of [1] to [4], wherein the (meth)acrylic polymer is a copolymer of monomer components comprising 50 to 99.8% by mass of alkoxyalkyl (meth)acrylate, 0.1 to 10% by mass of an amino group-containing monomer, and 0.1 to 10% by mass of a carboxy group-containing monomer.
[0013] [6] The aforementioned crosslinking agent is an epoxy-based crosslinking agent. An adhesive composition according to any one of [1] to [5], comprising 0.001 to 1 part by mass of the epoxy crosslinking agent per 100 parts by mass of the (meth)acrylic polymer.
[0014] [7] Furthermore, it contains polyalkylene glycols with a weight-average molecular weight of 100 to 12,000. An adhesive composition according to any one of [1] to [6], comprising 0.5 to 20 parts by mass of the polyalkylene glycol per 100 parts by mass of the (meth)acrylic polymer.
[0015] [8] An adhesive sheet having an adhesive layer formed from any of the adhesive compositions described in [1] to [7] on at least one surface of a substrate. [Effects of the Invention]
[0016] According to the present invention, it has been found that by including a temperature-responsive polymer in the adhesive composition, an adhesive sheet having an adhesive layer formed from the adhesive composition peels off quickly from the adherend in alkaline hot water. [Modes for carrying out the invention]
[0017] The adhesive composition and adhesive sheet of the present invention will be described below. In the present specification, acrylic and methacrylic are also collectively referred to as "(meth)acrylic". Further, in the present specification, "A to B" representing a numerical range means "A or more and B or less" unless otherwise specified.
[0018] [Pressure-sensitive Adhesive Composition] The pressure-sensitive adhesive composition of the present invention (hereinafter also referred to as "the present composition") contains a (meth)acrylic polymer, a temperature-responsive polymer having a lower critical solution temperature, and a crosslinking agent. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition exhibits excellent peelability, as the temperature-responsive polymer in the pressure-sensitive adhesive layer becomes insoluble and aggregation proceeds in the peeling step in warm alkaline water.
[0019] The present inventors believe that the reason for this is that the temperature-responsive polymer in the pressure-sensitive adhesive layer aggregates (gels) in warm alkaline water, partially reinforcing the pressure-sensitive adhesive layer, suppressing elution and disintegration of the pressure-sensitive adhesive layer, so that the sheet shape is maintained, and by receiving the stress of water flow from the edge of the pressure-sensitive adhesive layer, the pressure-sensitive adhesive sheet is peeled from the adherend more rapidly than peeling caused by disintegration of the pressure-sensitive adhesive layer. Therefore, compared with the conventional configuration in which the pressure-sensitive adhesive sheet is peeled from the adherend by gradually eluting into water and causing the pressure-sensitive adhesive layer to disintegrate, peeling can be completed in a shorter time.
[0020] [(Meth)acrylic Polymer] The (meth)acrylic polymer used in the present composition is a polymer composed of monomer components containing at least a (meth)acrylate ester. One or two or more kinds of the (meth)acrylic polymer may be used.
[0021] Examples of the (meth)acrylate ester include alkoxyalkyl (meth)acrylate, alkyl (meth)acrylate, alkoxypolyalkylene glycol mono(meth)acrylate, alicyclic group-containing (meth)acrylate, aromatic group-containing (meth)acrylate, and the like. One or two or more kinds of the (meth)acrylate ester may be used.
[0022] Examples of alkoxyalkyl (meth)acrylates include methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The number of carbon atoms in the alkoxyalkyl (meth)acrylate is usually 2 to 20, preferably 2 to 10, and more preferably 2 to 6.
[0023] Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, oleyl (meth)acrylate, n-stearyl (meth)acrylate, and isostearyl (meth)acrylate. The number of carbon atoms in the alkyl(meth)acrylate is usually 1 to 20, preferably 1 to 10, and more preferably 1 to 8.
[0024] Examples of alkoxy polyalkylene glycol mono(meth)acrylates include methoxydiethylene glycol mono(meth)acrylate, methoxydipropylene glycol mono(meth)acrylate, ethoxytriethylene glycol mono(meth)acrylate, ethoxydiethylene glycol mono(meth)acrylate, and methoxytriethylene glycol mono(meth)acrylate.
[0025] Examples of alicyclic group-containing (meth)acrylates and aromatic group-containing (meth)acrylates include cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate.
[0026] The (meth)acrylic acid ester preferably includes an alkoxyalkyl (meth)acrylate, from the viewpoint of improving the hydrophilicity of the (meth)acrylic polymer, making it more compatible with water, and enabling peeling in alkaline hot water in a short time.
[0027] In the monomer components used to synthesize the (meth)acrylic polymer, the proportion of (meth)acrylic acid ester used is preferably 50 to 99.9% by mass, more preferably 55 to 99% by mass, and even more preferably 60 to 97% by mass.
[0028] In one embodiment, the proportion of alkoxyalkyl (meth)acrylate used in 100% by mass of monomer components used to synthesize the (meth)acrylic polymer is preferably 50 to 99.9% by mass, more preferably 55 to 99.8% by mass, even more preferably 60 to 99% by mass, and particularly preferably 80 to 97% by mass, from the viewpoint of efficiently exhibiting the above effects.
[0029] The monomer components constituting the (meth)acrylic polymer preferably include a functional group-containing monomer. Examples of functional group-containing monomers include an amino group-containing monomer, a hydroxyl group-containing monomer, and a carboxyl group-containing monomer. One or more functional group-containing monomers may be used.
[0030] Examples of amino group-containing monomers include aminomethyl (meth)acrylate, aminoethyl (meth)acrylate, methylaminoethyl (meth)acrylate, ethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate, and diethylaminopropyl (meth)acrylate.
[0031] Examples of hydroxyl group-containing monomers include hydroxyalkyl(meth)acrylates such as 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, and 8-hydroxyoctyl(meth)acrylate; and N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-methylolacrylamide.
[0032] Examples of monomers containing a carboxyl group include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, mono(meth)acryloyloxyethyl succinate, ω-carboxypolycaprolactone mono(meth)acrylate, itaconic acid, crotonic acid, fumaric acid, and maleic acid.
[0033] When using a functional group-containing monomer, the proportion of the functional group-containing monomer used is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, and even more preferably 1 to 10% by mass, of 100% by mass of the monomer components used to synthesize the (meth)acrylic polymer. In this configuration, the resulting (meth)acrylic polymer tends to have a moderately crosslinked structure and an adhesive layer with moderate cohesive force.
[0034] Among the functional group-containing monomers, it is preferable that the monomers containing amino groups are included. At least some of the amino groups derived from amino group-containing monomers act as crosslinking sites in (meth)acrylic polymers, and can form a crosslinked structure (network polymer) by reacting with, for example, the epoxy groups of an epoxy crosslinking agent described later.
[0035] When an amino group-containing monomer is used as the functional group-containing monomer, the proportion of the amino group-containing monomer used is preferably 0.1 to 10% by mass, more preferably 0.3 to 8% by mass, and even more preferably 0.6 to 6% by mass, out of 100% by mass of the monomer components used to synthesize the (meth)acrylic polymer. When the proportion of the amino group-containing monomer used is within the above range, a sufficient crosslinking effect between the amino groups derived from the amino group-containing monomer and the crosslinking agent is obtained, and the crosslinked structure of the (meth)acrylic polymer is appropriately formed, resulting in an adhesive layer with appropriate tackiness and excellent peelability.
[0036] Among the functional group-containing monomers, it is also preferable to include carboxyl group-containing monomers. The proportion of carboxyl group-containing monomers used is preferably 0.1 to 10% by mass, more preferably 0.5 to 8% by mass, and even more preferably 1 to 7% by mass, out of 100% by mass of the monomer components used to synthesize the (meth)acrylic polymer.
[0037] By using the above range for the proportion of carboxyl group-containing monomers, when the adhesive sheet obtained from this composition is immersed in alkaline hot water during the peeling process, some or all of the carboxyl groups in the (meth)acrylic polymer are neutralized, improving the hydrophilicity of the (meth)acrylic polymer and making the adhesive layer more compatible with water. As a result, the temperature-responsive polymer in the adhesive layer becomes insoluble in hot water, promoting aggregation, and tends to peel off more easily from the edges of the tape, allowing for faster peeling. Furthermore, from the viewpoint of the tack of the adhesive sheet, it is preferable not to exceed the above range.
[0038] When functional group-containing monomers are used in combination with amino group-containing monomers and carboxy group-containing monomers, the catalytic effect of the amino group promotes the reaction between the carboxyl groups derived from the carboxyl group-containing monomer and the epoxy crosslinking agent. This tends to result in the formation of a crosslinked structure of the (meth)acrylic polymer to an appropriate degree, increasing the cohesive force of the adhesive layer and thus improving the adhesive layer's release properties with alkaline hot water.
[0039] A preferred embodiment of the (meth)acrylic polymer is a copolymer of monomer components containing 0.1 to 10% by mass of an amino group-containing monomer. Another preferred embodiment is a copolymer of monomer components comprising 50 to 99.8% by mass of alkoxyalkyl (meth)acrylate, 0.1 to 10% by mass of an amino group-containing monomer, and 0.1 to 10% by mass of a carboxy group-containing monomer. More preferably, the copolymer comprises 55 to 99.2% by mass of alkoxyalkyl (meth)acrylate, 0.3 to 8% by mass of an amino group-containing monomer, and 0.5 to 8% by mass of a carboxy group-containing monomer. Even more preferably, the copolymer comprises 60 to 98.4% by mass of alkoxyalkyl (meth)acrylate, 0.6 to 6% by mass of an amino group-containing monomer, and 1 to 7% by mass of a carboxy group-containing monomer.
[0040] The monomer components constituting the (meth)acrylic polymer may include other monomer components other than the (meth)acrylic acid ester and the functional group-containing monomer, to the extent that they do not impair the effects of the present invention.
[0041] Other monomer components include amide group-containing monomers such as (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylate, N-isopropylacrylamide, and N-methoxymethyl(meth)acrylamide; nitrogen atom-containing monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, and (meth)acryloylmorpholine; vinyl ester monomers such as vinyl acetate; and styrene monomers such as styrene, α-methylstyrene, and methylstyrene.
[0042] Other monomers may be used individually or in combination of two or more. The content of other monomers relative to 100% by mass of the monomer component constituting the (meth)acrylic polymer is preferably 0 to 49.8% by mass, more preferably 0 to 44.2% by mass, and particularly preferably 0 to 38.4% by mass.
[0043] [Physical properties of (meth)acrylic polymers] The weight-average molecular weight (Mw) of (meth)acrylic polymers, as measured by gel permeation chromatography (GPC), is, for example, 50,000 to 1,000,000 in polystyrene terms, preferably 100,000 to 500,000, and more preferably 100,000 to 300,000. By using (meth)acrylic polymers with an Mw in the above range, adhesive compositions with a viscosity suitable for coating can be easily obtained. When the Mw of the (meth)acrylic polymer is 50,000 or more, adhesive compositions with excellent repositionability tend to be obtained. When the Mw is 1,000,000 or less, the decrease in adhesive strength can be suppressed, and adhesive compositions with an excellent balance of adhesive properties (adhesion and ball tack) tend to be obtained. Details of the GPC measurement conditions are described in the Examples section below.
[0044] The glass transition temperature (Tg) of a (meth)acrylic polymer can be calculated, for example, from the polymerizable monomer units that constitute the polymer and their content ratios using Fox's formula. The Tg of a (meth)acrylic polymer obtained by Fox's formula is, for example, -70 to -10°C, preferably -60 to -20°C.
[0045] The glass transition temperatures of homopolymers composed of each polymerizable monomer in Fox's formula can be those listed, for example, in the Polymer Handbook Fourth Edition (Wiley-Interscience 2003).
[0046] [Meth)acrylic polymer manufacturing method] As for the method of producing the (meth)acrylic polymer used in this composition, any of the above-mentioned methods for polymerizing the monomer components can be employed, but production by bulk polymerization or solution polymerization is preferred. For example, polymerizable monomers are placed in a reaction vessel, a polymerization initiator is added, and the reaction is carried out at a reaction temperature of about 50 to 90°C for 2 to 20 hours. A polymerization solvent may be placed in the reaction as needed. The polymerization is carried out under an inert gas atmosphere such as nitrogen gas. In addition, polymerizable monomers, polymerization initiators, chain transfer agents, and polymerization solvents may be added as appropriate during the polymerization reaction.
[0047] Examples of polymerization initiators include azo compound-based polymerization initiators and peroxide-based polymerization initiators. One or more polymerization initiators can be used. The amount of polymerization initiator used is usually 0.001 to 2 parts by mass, preferably 0.002 to 1 part by mass, per 100 parts by mass of the polymerizable monomer.
[0048] Examples of azo compound polymerization initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), and 1,1'-azobis(cyclohexane-1-carbonitride).
[0049] Examples of peroxide-based polymerization initiators include tert-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-isopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and tert-butyl peroxybivalate.
[0050] Organic solvents are preferred as polymerization solvents. Examples of organic solvents include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, acetylacetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and sulfolane. One or more polymerization solvents can be used.
[0051] [Temperature-responsive polymers with a lower critical solution temperature] The temperature-responsive polymer having a lower critical solution temperature used in this composition is a polymer having a lower critical solution temperature (LCST) in water. The LCST (Low Temperature Saturation Temperature) is the temperature at which a polymer exhibits water solubility below a certain temperature, and above that temperature, it begins to become insoluble, resulting in turbidity, precipitation, and phase separation. Temperature-responsive polymers with an LCST undergo a phase transition at the LCST, exhibiting the property of reversibly changing between hydrophilic and hydrophobic properties. One or more temperature-responsive polymers having LCST can be used.
[0052] The temperature-responsive polymer is a polymer of a monomer component containing at least one selected from the group consisting of N-substituted (meth)acrylamide monomers and vinyl ether monomers. From the viewpoint of improving repositionability by reducing initial tack, a polymer of a monomer component containing an N-substituted (meth)acrylamide monomer is preferred. Polymers containing vinyl ether monomers tend to have a high initial tack.
[0053] Examples of N-substituted (meth)acrylamide monomers include N-isopropylacrylamide (LCST=32°C), Nn-propylmethacrylamide (LCST=32°C), N-ethoxyethylacrylamide (LCST=35°C), N-tetrahydrofurfurylmethacrylamide (LCST=35°C), N,N-diethylacrylamide (LCST=32°C), N-vinylbutylamide (LCST=32°C), N-vinylisobutylamide (LCST=39°C), N-cyclopropylacrylamide (LCST=46°C), and Nn-propylacrylamide. Examples include N-tetrahydrofurfurylacrylamide (LCST=28°C), N-isopropylmethacrylamide (LCST=44°C), Nn-propylmethacrylamide (LCST=28°C), N-methyl-N-isopropylacrylamide (LCST=23°C), N-methyl-Nn-propylacrylamide (LCST=20°C), N,N-dimethylaminoethyl methacrylate (LCST=47°C), N-tert-butylacrylamide (LCST=0°C), and N,N-ethylmethylacrylamide (LCST=56°C). The LCST of the monomer homopolymer in water is shown in parentheses to the right of each example monomer. The N-substituted (meth)acrylamide monomer can be one or more types.
[0054] Examples of vinyl ether monomers include vinyl methyl ether (LCST = 32°C), 2-methoxyethyl vinyl methyl ether (LCST = 64°C), and 4-hydroxybutyl vinyl ether (LCST = 40°C). The vinyl ether monomer can be one or more types.
[0055] The temperature-responsive polymer has a LCST preferably of 0 to 70°C, more preferably of 20 to 50°C, and even more preferably of 30 to 40°C. By using a temperature-responsive polymer with an LCST within this range, peeling can be performed in a short time in alkaline hot water (for example, an aqueous sodium hydroxide solution at 70°C). In the alkaline hot water, dehydration of the temperature-responsive polymer progresses, and aggregation (gelation) of the temperature-responsive polymer in the adhesive layer progresses rapidly, making it easier to peel from the edges of the adhesive layer, and allowing the peeling of the entire tape to proceed in a shorter time when subjected to the water flow. Details of the LCST measurement method will be described in the Examples section below.
[0056] The temperature-responsive polymer may be a polymer composed of only at least one monomer selected from the group consisting of N-substituted (meth)acrylamide monomers and vinyl ether monomers, or it may be a copolymer that, in addition to the aforementioned monomer, contains other monomer components, provided that the polymer exhibits temperature responsiveness and the LCST is in the range of 0 to 70°C. Generally, the LCST of a temperature-responsive polymer increases when the copolymerized monomers become hydrophilic (highly polar) and decreases when they become hydrophobic (lowly polar). Therefore, the LCST can be adjusted by changing the type and amount of monomers that make up the temperature-responsive polymer.
[0057] When the temperature-responsive polymer is a copolymer containing monomers other than N-substituted (meth)acrylamide monomers and vinyl ether monomers, it is more preferable that the polymer consists solely of at least one monomer selected from the group consisting of N-substituted (meth)acrylamide monomers and vinyl ether monomers, with at least 80% by mass or more, preferably 90% by mass or more, and more preferably 95% by mass or more, of the total monomer components used to form the temperature-responsive polymer.
[0058] If the temperature-responsive polymer is a copolymer obtained by polymerizing two or more monomers, it may be a random copolymer, a block copolymer, or a graft copolymer. The temperature-responsive polymer can be produced using conventionally known methods for polymerizing the monomer components described above, or a commercially available product may be used.
[0059] In this composition, the content of the temperature-responsive polymer is preferably 0.5 to 30 parts by mass, more preferably 1 to 25 parts by mass, even more preferably 3 to 20 parts by mass, and particularly preferably 4 to 15 parts by mass, per 100 parts by mass of the (meth)acrylic polymer. By containing 0.5 parts by mass or more of temperature-responsive polymer, the adhesive layer formed from the adhesive composition undergoes aggregation (gelation) of the temperature-responsive polymer in alkaline hot water, increasing the cohesive force of the adhesive layer and enabling peeling in a short time. When the content of the temperature-responsive polymer is 30 parts by mass or less, an adhesive composition with an excellent balance between the adhesive strength of the adhesive sheet and its peelability in alkaline hot water can be easily obtained.
[0060] [Physical properties of temperature-responsive polymers] The weight-average molecular weight (Mw) of the temperature-responsive polymer, as measured by gel permeation chromatography (GPC), is typically 500 to 200,000, preferably 1,000 to 100,000, in polystyrene equivalent. By using a temperature-responsive polymer with an Mw within this range, it is possible to easily balance the adhesive strength and create an adhesive composition with a viscosity suitable for coating. Details of the GPC measurement conditions are described in the Examples section below.
[0061] The glass transition temperature (Tg) of the temperature-responsive polymer can be calculated, for example, using Fox's formula based on the types of monomers constituting the polymer and their respective content ratios. From the viewpoint of adjusting the tackiness (adhesion, ball tack) to an appropriate range, the Tg of the temperature-responsive polymer is usually 0 to 200°C, preferably 40 to 150°C.
[0062] [Crosslinking agent] The crosslinking agent used in this composition is appropriately selected based on the crosslinkable groups that can be introduced into the (meth)acrylic polymer. Examples include epoxy crosslinking agents, metal chelate crosslinking agents, and isocyanate crosslinking agents. Epoxy crosslinking agents and metal chelate crosslinking agents are preferred, and epoxy crosslinking agents are even more preferred. By crosslinking (meth)acrylic polymers with a crosslinking agent, a crosslinked structure (network polymer) can be formed. One or more crosslinking agents may be used.
[0063] Examples of epoxy crosslinking agents include compounds having two or more epoxy groups in one molecule, such as ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidylaniline, diamineglycidylamine, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diamineglycidylaminomethyl), 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, sorbitol polyglycidyl ether, and castor oil polyglycidyl ether.
[0064] Examples of metal chelating crosslinking agents include compounds in which alkoxides, acetylacetone, acetate, etc., are coordinated to polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium. Specifically, examples include aluminum isopropylate, aluminum secondary butyrate, aluminum ethyl acetacetate / diisopropylate, aluminum trisethyl acetacetate, and aluminum trisacetylacetonate.
[0065] In this composition, the crosslinking agent content is preferably 0.001 to 1 part by mass, and more preferably 0.01 to 0.5 parts by mass, per 100 parts by mass of (meth)acrylic polymer. When the crosslinking agent content is 0.001 parts by mass or more, sufficient adhesive strength can be obtained, and there is a tendency to suppress overflow from the substrate and adhesive residue. When the crosslinking agent content is 1 part by mass or less, the crosslinking density does not become too high, a decrease in adhesive strength can be suppressed, and there is a tendency to obtain an adhesive composition with an excellent balance of adhesive properties (adhesion and ball tack).
[0066] [Polyalkylene glycol] This composition may contain polyalkylene glycol. Due to its high hydrophilicity, polyalkylene glycol facilitates the dispersion of moisture that penetrates the adhesive layer during the alkaline hot water peeling process, resulting in rapid temperature-responsive polymer aggregation (gelation). An adhesive layer formed from an adhesive composition containing polyalkylene glycol ensures excellent alkaline hot water peelability while simultaneously achieving both high adhesive properties (adhesion and ball tack). One or more types of polyalkylene glycols may be used.
[0067] Examples of polyalkylene glycols include polypropylene glycol, polyethylene glycol, poly(ethylene oxide / propylene oxide) block copolymer, poly(ethylene oxide / propylene oxide) random copolymer, and polytetramethylene glycol, with polypropylene glycol and polyethylene glycol being preferred.
[0068] The weight-average molecular weight (Mw) of polyalkylene glycol, measured by gel permeation chromatography (GPC), is typically 100 to 12,000 in polystyrene terms. From the viewpoint of alkaline hot water release properties and adhesive strength, a value of 100 to 10,000 is preferred, and 200 to 8,000 is more preferred. Details of the GPC measurement conditions are described in the Examples section below. When using commercially available polyalkylene glycol, the Mw value should be prioritized based on the catalog value of the commercially available product.
[0069] In this composition, the polyalkylene glycol content is 0.5 to 20 parts by mass, more preferably 1 to 15 parts by mass, and even more preferably 3 to 13 parts by mass, per 100 parts by mass of (meth)acrylic polymer. When the polyalkylene glycol content is within the above range, an adhesive composition with excellent alkaline hot water release properties and tackiness tends to be obtained.
[0070] [Additives] In addition to the above components, this composition may contain one or more additives selected from antioxidants, light stabilizers, metal corrosion inhibitors, tackifiers, plasticizers, crosslinking accelerators, surfactants, defoamers, fillers, wettability modifiers, dyes, pigments, colorants, antistatic agents, etc., to the extent that they do not impair the effects of the present invention. If additives are included, their content is 0.01 to 30 parts by mass, preferably 0.01 to 20 parts by mass, per 100 parts by mass of (meth)acrylic polymer.
[0071] [Preparation of adhesive composition] This composition can be prepared by mixing a (meth)acrylic polymer, a temperature-responsive polymer, a crosslinking agent, and, if necessary, other components such as polyalkylene glycol and additives, using conventionally known methods. In addition to the above components, organic solvents may also be included, as long as they do not impair the effects of the present invention. Examples of organic solvents include those similar to polymerization solvents used in the production of (meth)acrylic polymers. For example, one method involves blending a temperature-responsive polymer, a crosslinking agent, and other components such as polyalkylene glycol or additives, as needed, into a polymer solution containing a (meth)acrylic polymer obtained during the synthesis of the (meth)acrylic polymer.
[0072] [Adhesive sheet] In one embodiment, the adhesive sheet of the present invention may have an adhesive layer formed from the above-described composition on at least one surface of a substrate. Examples of adhesive sheets include a double-sided adhesive sheet having a substrate and the adhesive layer formed on both sides of the substrate; a single-sided adhesive sheet having a substrate and the adhesive layer formed on one side of the substrate; and adhesive sheets in which a release liner, which has been peeled off, is attached to the side of the adhesive layer of the adhesive sheet that is not in contact with the substrate.
[0073] The substrate supporting the adhesive layer is not particularly limited, and for example, plastic film, paper, cloth, rubber sheet, foam sheet, metal foil, and composites thereof can be used.
[0074] Examples of plastic films include polyester films such as polyethylene terephthalate (PET); polyolefin films such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymer; plastic films made from materials such as polyvinyl chloride, polyurethane, and nylon; and heat-shrinkable films (shrink films) made from the aforementioned materials.
[0075] Examples of paper include washi (Japanese paper), high-quality paper, synthetic paper (Yupo), kraft paper, art paper, coated paper, thermal paper, and water-soluble paper.
[0076] Examples of fabrics include woven and nonwoven fabrics made from various fibrous materials, either individually or in blends.
[0077] Examples of metal foils include aluminum foil and copper foil. Among these, art paper and water-soluble paper are preferred because they are easily peeled off the adherend.
[0078] The thickness of the substrate is not particularly limited, but is usually 10 to 200 μm, preferably 25 to 150 μm. The substrate may be colored or colorless. Furthermore, at least one surface of the substrate may be printed or marked. That is, at least one surface of the substrate may be provided with a thermal recording layer, a printable image receiving layer capable of thermal transfer, inkjet, or laser printing, a printability improving layer, etc. Furthermore, the substrate may be subjected to treatments such as corona treatment or plasma discharge treatment, and may also be coated with an anchor coating material.
[0079] The release liner is not particularly limited; it is not limited as long as it can be easily peeled off from the adhesive layer, and materials similar to those mentioned above for the base material can be used. The film thickness of the release liner is not particularly limited, but is usually 10 to 500 μm, preferably 20 to 200 μm. Furthermore, to improve the release properties of the adhesive layer, at least one side of the surface of the release liner may be provided with an easy-release treatment layer using a release agent such as a silicone-based, fluorine-based, long-chain alkyl-based, or aliphatic amide-based agent.
[0080] For general use as an adhesive sheet, the adhesive strength to polypropylene boards is preferably 1.5 N / 20 mm or more, more preferably 2.0 N / 20 mm or more, and even more preferably 3.0 N / 20 mm or more. The upper limit is preferably 20 N / 20 mm or less, and more preferably 10 N / 20 mm or less. Having the adhesive strength to polypropylene boards within this range allows the adhesive tape to exhibit sufficient adhesion and enables general use on a variety of substrates. For general use as an adhesive sheet, the ball tack is preferably 3 or higher, more preferably 5 or higher, and even more preferably 8 or higher. From the viewpoint of initial repositionability, the upper limit is preferably 30 or less, more preferably 25 or less, and even more preferably 20 or less.
[0081] The adhesive layer is formed from the above-described composition. For example, the adhesive layer is obtained by advancing the crosslinking reaction in the above-described composition, specifically by crosslinking a (meth)acrylic polymer with a crosslinking agent.
[0082] The conditions for forming the adhesive layer are, for example, as follows: The adhesive layer may be formed by directly applying the composition onto the substrate, or an adhesive layer may be formed on a release liner and then bonded to the substrate. Specifically, one method involves applying the composition onto a release liner, drying it, and then transferring the adhesive layer made of the composition to the substrate.
[0083] The drying conditions are not particularly limited and vary depending on the type of solvent, but are usually 50-150°C, preferably 60-100°C, and are dried for 1-10 minutes, preferably 2-7 minutes, to remove the solvent and form an adhesive layer. After the subsequent drying process, a curing period may be provided. If a curing period is provided, the conditions are usually 5-80°C, 5-70% RH environment, and 1-10 days.
[0084] The thickness of the adhesive layer (film thickness after drying) is typically 5 to 100 μm, preferably 10 to 60 μm.
[0085] As a method for applying the adhesive composition, known methods such as spin coating, knife coating, roll coating, bar coating, blade coating, die coating, and gravure coating can be used to apply the composition to a predetermined thickness.
[0086] The adhesive sheet of the present invention is suitably used as a label to be affixed to various containers, such as glass bottles like beer bottles and liquor bottles, and plastic bottles like PET bottles. Furthermore, since it can be easily peeled off the adherend in alkaline hot water after use, it is useful as a label for reusable containers.
[0087] For general use as a label for containers, the peeling time of the adhesive sheet from the glass in the peeling process using alkaline hot water (e.g., a sodium hydroxide aqueous solution at 70°C) is preferably 3 minutes 30 seconds or less, more preferably 3 minutes or less, even more preferably 2 minutes 30 seconds or less, and particularly preferably 2 minutes or less. A peeling time within this range allows the label to be used for reusable containers. Details of the method for measuring the peeling time in alkaline hot water will be described in the Examples section below. [Examples]
[0088] The present invention will be described more specifically below based on examples, but the present invention is not limited in any way to these examples. In the following descriptions of examples, unless otherwise specified, "parts" refers to "parts by mass".
[0089] [Manufacturing Example 1] In a reactor equipped with a stirrer, reflux condenser, thermometer, and nitrogen inlet tube, 96 parts of methoxyethyl acrylate (MEA), 1 part of dimethylaminoethyl methacrylate (DM), 3 parts of acrylic acid (AA), and 130 parts of ethyl acetate were charged, and the temperature was raised to 75°C while introducing nitrogen gas. Next, 0.1 parts of 2,2'-azobisisobutyronitrile was added, and the polymerization reaction was carried out under a nitrogen atmosphere at 75-76°C for 4 hours to obtain a solution containing (meth)acrylic polymer (a1). The Mw of (meth)acrylic polymer (a1) was 150,000, and the Tg was -46.7°C (calculated using Fox's formula).
[0090] [Manufacturing Examples 2-8] A solution containing (meth)acrylic polymers (a2) to (a8) was obtained in the same manner as in Production Example 1, except that the types and amounts of monomer components used were changed as shown in Table 1 below.
[0091] [Table 1]
[0092] MEA: 2-Methoxyethyl acrylate BA: n-butyl acrylate DM: Dimethylaminoethyl methacrylate AA: Acrylic acid
[0093] [Manufacturing Example 9] In a reaction apparatus equipped with a stirrer, reflux condenser, thermometer, and nitrogen inlet tube, 100 parts of N,N-diethylacrylamide (DEAA) and 225 parts of ethyl acetate were charged, and the polymerization reaction was carried out for 1 hour and 30 minutes at a temperature of 75°C while introducing nitrogen gas. Next, 0.1 parts of 2,2'-azobisisobutyronitrile were added, and the polymerization reaction was carried out at 80°C for 2 hours and 30 minutes under a nitrogen atmosphere to obtain a solution containing the temperature-responsive polymer (b1) (pDEAA). The Mw of the temperature-responsive polymer (b1) was 18,000, the Tg was 81°C, and the LCST was 32°C.
[0094] [Manufacturing Example 10] The preparation was carried out in the same manner as in Preparation Example 9, except that the N-substituted (meth)acrylamide monomer was replaced with N-isopropylacrylamide (NIPAM) and the solvent was changed to methyl ethyl ketone, to obtain a solution containing the temperature-responsive polymer (b2) (pNIPAM). The Mw of the temperature-responsive polymer (b2) was 0.16 million, the Tg was 130°C, and the LCST was 32°C.
[0095] [Evaluation: Weight-average molecular weight (Mw)] For (meth)acrylic polymers and temperature-responsive polymers, the Mw (millimeters of styrene) was determined in terms of standard polystyrene using gel permeation chromatography (GPC) under the following conditions. • Measuring device: HLC-8120GPC (manufactured by Tosoh) • GPC column configuration: The following five-column array (all manufactured by Tosoh) (1) TSK-GEL HXL-H (Guard Column) (2) TSK-GEL G7000HXL (3) TSK GEL GMHXL (4) TSK-GEL GMHXL (5) TSK-GEL G2500HXL • Sample concentration: 1.0 mg / cm³ 3 Dilute with tetrahydrofuran to achieve the following result. • Mobile phase solvent: tetrahydrofuran ·Flow rate: 1.0cm 3 / min Column temperature: 40°C
[0096] [Evaluation: Lower Critical Solution Temperature (LCST)] The LCST of temperature-responsive polymers was measured using a V-650 UV-Vis-Near Infrared spectrophotometer (manufactured by JASCO Corporation) with a variable temperature function, according to the following method. The temperature-responsive polymer was prepared as a 1% by mass aqueous solution, and the change in the transmittance of the aqueous solution (wavelength 500 nm) was measured when the temperature was increased from 5°C at 1°C / min. The temperature at which the transmittance decreased from the initial transmittance to 50% was defined as the LCST.
[0097] [Example 1] To 100 parts of the solids content of the solution containing the (meth)acrylic polymer (a1) obtained in Production Example 1, a solution containing the temperature-responsive polymer (b1) obtained in Production Example 9 was added in an amount equal to 10 parts of the solids content of the temperature-responsive polymer (b1), and 0.03 parts of Denacol EX-614 (sorbitol polyglycidyl ether, manufactured by Nagase ChemteX) was added as an epoxy crosslinking agent to obtain an adhesive composition.
[0098] [Examples 2-20, Comparative Example 2] An adhesive composition was obtained in the same manner as in Example 1, except that the formulation was changed as described in Tables 2-1 to 2-2.
[0099] [Making adhesive sheets] The adhesive compositions obtained in the examples and comparative examples were applied to a release liner of polyethylene terephthalate with a thickness of 25 μm that had been subjected to a release treatment, so that the thickness after drying was 25 μm. The mixture was dried at 90°C for 3 minutes to remove the solvent and form an adhesive layer with a thickness of 25 μm. A 65 μm thick sheet of water-soluble paper 30MDP (manufactured by Nippon Paper Industries Papilia) was attached to the surface of the adhesive layer opposite to the surface in contact with the release liner to obtain an adhesive sheet having an adhesive layer with a thickness of 25 μm.
[0100] [Evaluation: Adhesion] The obtained adhesive sheets were cut to a width of 20 mm to prepare test specimens. The release liner, which had been treated for release, was peeled off the test specimens, and the exposed adhesive layer was attached to a polypropylene board by rolling a 2 kg roller back and forth three times. After standing for 20 minutes at 23°C and 50% RH, the adhesive strength was measured when the sheet was peeled off at a peeling angle of 180° and a tensile speed of 300 mm / min. The peeling morphology of the adhesive layer was also observed visually. If the adhesive layer peeled off without adhering to the polypropylene board, it was indicated as "af," and if part of the adhesive layer peeled off while adhering to the polypropylene board, it was indicated as "dirty." The results are shown in Tables 2-1 to 2-2.
[0101] [Rating: Ball Tack] Measurements were taken using the J. Dow method. Specifically, the release liner was peeled off the prepared adhesive sheet and attached to an inclined surface with a 30° angle so that the adhesive layer was exposed. Next, under conditions of 23°C and 50% RH, a steel ball was launched from the top of the inclined surface and then slid across the adhesive surface (adhesive layer surface). The launch distance was 10 cm and the sliding distance was 10 cm. Sliding tests were performed with varying diameters of steel balls, and the maximum diameter of the steel ball that stopped sliding on the adhesive surface was determined. The diameter of the steel balls used was X / 32 inches (where X is an integer from 1 to 32), and the values shown in Tables 2-1 to 2-2 represent the value of X.
[0102] [Evaluation: Alkaline hot water peeling properties] The obtained adhesive sheet was cut to a width of 20 mm and a length of 50 mm to prepare test specimens. The release liner was peeled off the test specimen, and the exposed adhesive layer was attached to a glass plate by rolling a 2 kg roller back and forth three times. The specimens were then autoclaved (50°C, 5 atm, 20 minutes) and left to stand for 1 hour at 23°C and 50% RH. The test solution (2.5% sodium hydroxide aqueous solution) was placed in a separable flask equipped with a stirring blade, and the solution temperature was maintained at 70°C and stirred at a rotation speed of 200 rpm. The glass plate with the attached test specimen was immersed in the stirring test solution. The time (minutes:seconds) from the start of immersion until the test specimen separated from the glass plate was evaluated. The evaluation was performed twice, and the average value was calculated. The results are shown in Tables 2-1 to 2-2.
[0103] [Table 2-1]
[0104] [Table 2-2]
[0105] VME-70T: Polyvinyl methyl ether (LCST=34℃) (Polyvinyl methyl ether 70T, manufactured by Senka), Mw 70,000, Tg=49℃ PEG-300:Mw300 polyethylene glycol (manufactured by Sanyo Chemical Industries) PEG-600:Mw600 polyethylene glycol (manufactured by Sanyo Chemical Industries) PEG-10000:Mw10,000 polyethylene glycol (manufactured by Sanyo Chemical Industries)
Claims
1. The material comprises a (meth)acrylic polymer, a temperature-responsive polymer having a lower critical solution temperature, and a crosslinking agent. The temperature-responsive polymer is a polymer of a monomer component comprising at least one selected from the group consisting of N-substituted (meth)acrylamide monomers and vinyl ether monomers, in an adhesive composition.
2. The adhesive composition according to claim 1, comprising 0.5 to 30 parts by mass of the temperature-responsive polymer per 100 parts by mass of the (meth)acrylic polymer.
3. The adhesive composition according to claim 1, wherein the temperature-responsive polymer is a polymer of a monomer component containing the N-substituted (meth)acrylamide monomer.
4. The adhesive composition according to claim 1, wherein the (meth)acrylic polymer is a copolymer of monomer components containing 0.1 to 10% by mass of an amino group-containing monomer.
5. The adhesive composition according to claim 1, wherein the (meth)acrylic polymer is a copolymer of monomer components comprising 50 to 99.8% by mass of alkoxyalkyl (meth)acrylate, 0.1 to 10% by mass of an amino group-containing monomer, and 0.1 to 10% by mass of a carboxy group-containing monomer.
6. The aforementioned crosslinking agent is an epoxy-based crosslinking agent. The adhesive composition according to claim 1, comprising 0.001 to 1 part by mass of the epoxy crosslinking agent per 100 parts by mass of the (meth)acrylic polymer.
7. Furthermore, it contains polyalkylene glycol with a weight-average molecular weight of 100 to 12,000. The adhesive composition according to claim 1, comprising 0.5 to 20 parts by mass of the polyalkylene glycol per 100 parts by mass of the (meth)acrylic polymer.
8. An adhesive sheet having an adhesive layer formed from the adhesive composition described in any one of claims 1 to 7 on at least one surface of a substrate.
Citation Information
Patent Citations
Pressure-sensitive adhesive composition and method for utilizing the same
JP1998226776A
Hot water peelable label
JP2002140008A